2013
DOI: 10.3892/ijmm.2013.1310
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β-induced matrix metalloproteinase-9 secretion is associated with retinal pigment epithelial barrier disruption

Abstract: Local and chronic inflammation induced by amyloid-β (Aβ) plays a central role in the development of age-related macular degeneration. The retina is an immune-privileged site due to local tissue barrier. Yet, the manner by which immune cells pass through this barrier and accumulate in the retina remains unclear. Matrix metalloproteinases (MMPs) induce barrier disruption via proteolysis of epithelial tight junction (TJ) proteins. We hypothesized that Aβ-induced MMP secretion causes disruption of epithelial barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
(50 reference statements)
1
16
0
Order By: Relevance
“…Oligomerized Aβ (OAβ) was synthesized as previously described (11). Briefly, lyophilized Aβ 1-42 peptide (Sigma-Aldrich, USA) was dissolved in 1.5 M hexafluoroisopropanol (HFIP) on ice and aliquoted at -20°C.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Oligomerized Aβ (OAβ) was synthesized as previously described (11). Briefly, lyophilized Aβ 1-42 peptide (Sigma-Aldrich, USA) was dissolved in 1.5 M hexafluoroisopropanol (HFIP) on ice and aliquoted at -20°C.…”
Section: Methodsmentioning
confidence: 99%
“…The donors were between 30 and 40 years of age and none had a history of eye disease. Human RPE cells were harvested as described previously (11). In brief, whole eyes were cleaned in 0.9% NaCl solution, immersed in 5% polyvinylpyrrolidone iodine, and rinsed again in NaCl solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, under pathological conditions, the expression level of MMP-2 is raised by stimulating factors, such as tissue injury and inflammation [38,39]. Disruption of the ECM caused by an imbalance of MMP-2 and its inhibitors leads to a further series of histopathological changes, including inflammatory infiltration and retinal cell apoptosis [40,41,42]. Previous studies of experimental autoimmune uveitis have demonstrated that MSCs display their immunomodulatory and therapeutic properties in a paracrine fashion [43,44].…”
Section: Discussionmentioning
confidence: 99%